FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEPMENKES NO.1087/MENKES/SK/VIII/2010 TENTANG KESELAMATAN DAN KESEHATAN KERJA DI RUMAH SAKIT - Mgs. M. Ilyas (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Hospitals have the purpose of providing personal health services in plenary that is promotive, preventive, curative, and rehabilitative services in order to realize the degree of public health as high. In fact in achieving the goals of the hospital above are some factors that influence one human safety and health of the hospital itself. SDM is dominant in achieving the hospital for how health care is given to the maximum by the hospital human resources in order to achieve the degree of public health as high if they themselves in a state that is not safe and not healthy. Based on the description above, the researchers are interested in making the observation and analysis of the factors that affect the implementation Kepmenkes no.1087 / Menkes / SK / VIII / 2010 on occupational safety and health in the hospital.The method used is descriptive qualitative, aimed to provide an overview